Mediators of the Age Effect in the Carotid Revascularization Endarterectomy Versus Stenting Trial (CREST). Issue 10 (October 2015) - Voeks, Jenifer H.; Howard, George; Roubin, Gary; Farb, Richard; Heck, Donald; Logan, William; Longbottom, Mary; Sheffet, Alice; Meschia, James F.; Brott, Thomas G.
Abstract : Background and Purpose—: There is higher combined risk of stroke or death (S+D) at older ages with carotid stenting. We assess whether this can be attributed to patient or arterial characteristics that are in the pathway between older age and higher risk. Methods—: Mediation analysis of selected patient (hypertension, diabetes mellitus, and dyslipidemia) and arterial characteristics assessed at the clinical sites and the core laboratory (plaque length, eccentric plaque, ulcerated plaque, percent stenosis, peak systolic velocity, and location) was performed in 1123 carotid artery stenting–treated patients in the Carotid Revascularization Endarterectomy Versus Stenting Trial (CREST). We assessed the association of age with these characteristics, the association of these characteristics with stroke risk, and the amount of mediation of the association of age on the combined risk of periprocedural S+D with adjustment for these factors. Results—: Only plaque length as measured at the sites increased with age, was associated with increased S+D risk and significantly mediated the association of age on S+D risk. However, adjustment for plaque length attenuated the increased risk per 10 years of age from 1.72 (95% confidence interval, 1.26–2.37) to 1.66 (95% confidence interval, 1.20–2.29), accounting for only 8% of the increased risk. Conclusions—: Plaque length seems to be in the pathway between older age and higher risk of S+D among carotid artery stenting–treated patients, but it mediated only 8% of the age effect excess risk of carotid artery stenting in CREST. Other factors and mechanisms underlying the age effect need to be identified as plaque length will not identify elderly patients for whom stenting is safe relative to endarterectomy. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT00004732.